HA198 mutations in H9N2 avian influenza: molecular dynamics insights into receptor binding - Zhu, Rui; Wu, Jie; Chen, Ruiying; Zhou, Mo; Cao, Shinuo; Wu, Zhi; Wang, Ligang; Zhang, Lei; Zhu, Shanyuan (Frontiers in Veterinary Science, 2025)
IntroductionThe H9N2 avian influenza virus is widely disseminated in poultry and poses a zoonotic threat, despite vaccination efforts. Mutations at residue 198 of hemagglutinin (HA) are critical for antigenic variation and receptor-binding specificity, but the underlying molecular mechanisms remain unclear. This study explores the molecular mechanisms by which mutations at the HA 198 site affect the antigenicity, receptor specificity, and binding affinity of the H9N2 virus.MethodsUsing the sequence of the A/Chicken/Jiangsu/WJ57/2012 strain, we constructed recombinant H9N2 viruses, including rWJ57, rWJ57/HA198A, and rWJ57/HA198T, using reverse genetics. These variants were analyzed through hemagglutination inhibition (HI) assays, receptor-destroying enzyme (RDE) assays, enzyme-linked immunosorbent assays (ELISA) and solid-phase receptor binding assays. Additionally, molecular dynamics (MD) simulations were performed to further dissect the atomic-level interactions between HA and sialic acids (SA).ResultsThe results demonstrated that HA mutations significantly altered the receptor-binding properties of the virus. Specifically, rWJ57 (HA198V) exhibited 4-fold and 16-fold higher overall receptor-binding avidity compared to rWJ57/HA198A and rWJ57/HA198T, respectively. Furthermore, HA198V/T mutations significantly enhanced viral binding to human-type α2,6 SA receptors (p < 0.001), whereas the HA198A mutation exhibited a marked preference for avian-type α2,3 SA receptors (p < 0.001). Additionally, these mutations altered interactions with non-specific antibodies but not specific antibodies, with high-avidity receptor binding mutations exhibiting reduced non-specific antibody binding, suggesting a potential novel mechanism for immune evasion. MD simulations revealed HA198V/T formed stable complexes with the α2,6 SA, mediated by specific residues and water bridges, whereas HA198A formed stable complexes with the α2,3 SA. Interestingly, residue 198 interacted with the α2,6 SA via water bridges but had with showed minimal direct interaction with α2,3 SA.DiscussionThis study provides new insights into the molecular basis of receptor specificity, binding affinity, and antigenic drift in H9N2 viruses, highlighting the critical role of HA 198 mutations in regulating host adaptation. These findings are of great significance for H9N2 virus surveillance, vaccine development, and zoonotic transmission risk assessment.